WAWANCARA SEBAGAI SALAH SATU ALAT SELEKSI - Christine W Sandroto (Bina Ekonomi, 1999)
To determine which applicants should be hired, selection process must be done' property. Many selection tools can be used, but all of them should be reliable and valid. One of  Many selection fools is the selection interview. The selection interview is a conversation Between applicants and employer that is designed to predict applicants' acceptability. For Improving reliability and validity in the interview, the interviewer has to understand about the Content of the interview and know how to conduct it. So, the interviewer must have sufficient Knowledge about the vacant job. Without sufficient knowledge, there is a great possibility that The result of the interview with be a hiring decision that is not valid. About conducting the interview, the interviewer should cover the topics of the interview well and asking with the Right questions (content). The interviewer should be careful about applicants game-playing During the interview and keep watching out against bias possibly from him or herself.